Four Byzantine novels - Jeffreys, Elizabeth, 1941-; Jeffreys, Elizabeth, 1941-; Jeffreys, Elizabeth, 1941-; Prodromos, Theodóros, asi 1100-asi 1158.; Eustathios Makrembolités, činný 12. století.; Manassés, Konstantinos, -1187.; Nikétas Eugenianos, činný 12. století. (Translated texts for byzantinists, 2012)
Constantinople in the mid-twelfth century saw the composition of the first sustained fictional narratives in the European world – novels – since late antiquity. Four members of the Byzantine intelligentsia produced for the entertainment of their colleagues, their aristocratic patrons, and not least themselves, pastiches in verse and prose of the romantic tales of Achilles Tatius and Heliodorus. These novels are perhaps the most attractive, as well as the most unexpected, literary products of the Byzantine millennium. More than one of the four novels translated here was well known in Renaissance Europe, but all have been largely neglected by later generations of readers and scholars as insipid and derivative eroticism. This is regrettable since they antedate by several decades the works of Chrétien de Troyes, the French father of the European novel. This Byzantine phase in the history of the genre, though not part of its central development, deserves exploration.